PERTUMBUHAN BIBIT TANAMAN KELOR (Moringa oleifera Lam.) ASAL BIJI PADA BERBAGAIFASE PINDAH TANAM SEMAI - Samsul Hilal; I Gusti Made Arya Parwata; Bambang Budi Santoso (LPPM Universitas Mataram, 2018)
This research was aimed to find out the growth of seedling drum stick (Moringa oleifera Lam.). originatedfrom seed at different phases of transplanting. Has been done on aplir – juli 2017 at Dasanagung, Mataram, West Nusa Tenggara. This study used a complete randomized design (CRD) of one factor, namely: direct seed planting, fishing phase, needle phase, bud phase, and the first leaf phase blooms perfect. The results of this study showed that phase of transplanting has no significant effect on growth of seedling moringa plant. Both of fhising phase and needle phase are better of five transplanting’s phase.